Leukoaraiosis Distribution and Cerebral Collaterals: A Systematic Review and Meta-Analysis - Xu, Mangmang; Guo, Wen; Rascle, Lucie; Mechtouff, Laura; Nighoghossian, Norbert; Eker, Omer; Wang, Lu; Henninger, Nils; Mikati, Abdul Ghani; Zhang, Shihong; Wu, Bo; Liu, Ming (Frontiers in Neurology, 2022)
Background and Objective Microvascular failure might result in the collapse of cerebral collaterals. However, controversy remains regarding the role of leukoaraiosis (LA) in collateral recruitment. We, therefore, performed a systematic review and meta-analysis of the association between LA and cerebral collaterals. Methods Ovid Medline, PubMed, Embase, Web of Science, and three Chinese databases were searched from inception to August 2021. Two types of cerebral collaterals, including Circle of Willis (CoW) and leptomeningeal collaterals (LC), were investigated separately. Random effect models were used to calculate the pooled odds ratio (OR). Meta-regression and subgroup analyses were performed to explore the potential sources of heterogeneity. Results From 14 studies (n = 2,451) that fulfilled our inclusion criteria, data from 13 could be pooled for analysis. Overall, there was a significant association between severe LA and incomplete CoW (pooled OR 1.66, 95% CI 1.18–2.32, p = 0.003), with low heterogeneity (I2 = 5.9%). This association remained significant in deep LA (pooled OR 1.48, 95% CI 1.04–2.11, p = 0.029, I2 = 0), but not periventricular LA. Similarly, there was a significant association between LA and LC (pooled OR 1.73, 95% CI 1.03–2.90, p = 0.037), but with high heterogeneity (I2 = 67.2%). Meta-regression indicated a negative association of sample size with the effect sizes (p = 0.029). In addition, most of the studies (7/9) included into the analysis of the relationship of severe LA with poor LC enrolled subjects with large vessel occlusion stroke, and this relationship remained significant when pooling the seven studies, but with high heterogeneity. Conclusion Severe LA is associated with a higher prevalence of poor collaterals. This association is robust for CoW but weak for LC. Further studies are required to explore the underlying mechanisms.